Nanoparticle-based drug delivery systems for the treatment of cardiovascular diseases - Yang, Fangyu; Xue, Jianjiang; Wang, Guixue; Diao, Qizhi (Frontiers in Pharmacology, 2022)
Cardiovascular disease is the most common health problem worldwide and remains the leading cause of morbidity and mortality. Despite recent advances in the management of cardiovascular diseases, pharmaceutical treatment remains suboptimal because of poor pharmacokinetics and high toxicity. However, since being harnessed in the cancer field for the delivery of safer and more effective chemotherapeutics, nanoparticle-based drug delivery systems have offered multiple significant therapeutic effects in treating cardiovascular diseases. Nanoparticle-based drug delivery systems alter the biodistribution of therapeutic agents through site-specific, target-oriented delivery and controlled drug release of precise medicines. Metal-, lipid-, and polymer-based nanoparticles represent ideal materials for use in cardiovascular therapeutics. New developments in the therapeutic potential of drug delivery using nanoparticles and the application of nanomedicine to cardiovascular diseases are described in this review. Furthermore, this review discusses our current understanding of the potential role of nanoparticles in metabolism and toxicity after therapeutic action, with a view to providing a safer and more effective strategy for the treatment of cardiovascular disease.